The relationship between Egypt and Islamicjerusalem in the light of the Theories of the Circles of the Baraka and Geopolitics - Al- Ja'bari, Tariq Abdel Fattah (Arab Journal for Sciences and Research Publishing, 2018)
The study deals with the relationship between Egypt and Islamicjerusalem in the light of the geopolitics theory. The study follows the historical and descriptive approach to a better understanding of reality and inspiration for the future. Egypt and Palestine have an organic relationship throughout history. Both countries have had a major impact on the events of the two countries. The historical interpretations of this relationship differed without providing an explanation or an integrated model for the understanding of contemporary developments. Hence, the approaches of the geopolitics theories and models emerged. The main question was: What is the nature of the relationship between Egypt and Islamicjerusalem in the light of geopolitics? Many of the previous studies have dealt with the contemporary events of the twentieth century as a conflict between the Palestinians and the Zionist movement and the British occupation. Consequently, the Palestinians carried the bulk of the results of the studies, as well as the injustice of the events on the ground. If the study of the Zionist movement in isolation from the Western supportive framework, and this study deals with the Palestinian issue from the concept of Islamicjerusalem from the perspective of Geopolitics, and hopes to achieve the research goals, including: a statement of the historical background between Islamicjerusalem and Egypt, And the definition of the importance of Egypt to the Islamicjerusalem and its future role in the liberation of Islamicjerusalem inspired by the understanding of this relationship and the experiences of history
Keywords: Jerusalem; Egypt; Geopolitics; The Palestinian Question